Ataxia-Telangiectasia Locus: Sequence Analysis of 184 kb of Human Genomic DNA Containing the Entire ATM Gene - Platzer, Matthias; Rotman, Galit; Bauer, David; Uziel, Tamar; Savitsky, Kinneret; Bar-Shira, Anat; Gilad, Shlomit; Shiloh, Yosef; Rosenthal, André (Genome Research, 1997)
Ataxia-telangiectasia (A-T) is an autosomal recessive disorder involving cerebellar degeneration, immunodeficiency, chromosomal instability, radiosensitivity, and cancer predisposition. The genomic organization of the A-T gene, designatedATM, was established recently. To date, more than 100 A-T-associated mutations have been reported in the ATM gene that do not support the existence of one or several mutational hotspots. To allow genotype/phenotype correlations it will be important to find additional ATM mutations. The nature and location of the mutations will also provide insights into the molecular processes that underly the disease. To facilitate the search for ATMmutations and to establish the basis for the identification of transcriptional regulatory elements, we have sequenced and report here 184,490 bp of genomic sequence from the human 11q22–23 chromosomal region containing the entire ATM gene, spanning 146 kb, and 10 kb of the 5′-region of an adjacent gene named E14/NPAT.The latter shares a bidirectional promoter with ATM and is transcribed in the opposite direction. The entire region is transcribed to ∼85% and translated to 5%. Genome-wide repeats were found to constitute 37.2%, with LINE (17.1%) and Alu (14.6%) being the main repetitive elements. The high representation of LINE repeats is attributable to the presence of three full-length LINE-1s, inserted in the same orientation in introns 18 and 63 as well as downstream of the ATM gene. Homology searches suggest that ATM exon 2 could have derived from a mammalian interspersed repeat (MIR). Promoter recognition algorithms identified divergent promoter elements within the CpG island, which lies between the ATM andE14/NPAT genes, and provide evidence for a putative secondATM promoter located within intron 3, immediately upstream of the first coding exon. The low G + C level (38.1%) of theATM locus is reflected in a strongly biased codon and amino acid usage of the gene.[The sequence data described in this paper have been submitted to the GenBank data library under accession no. U82828.]
10.1101/gr.7.6.592